UJI SENSITIVITAS PROPOLIS TERHADAP BAKTERI Staphylococcus aureus Dan Eschericia coli - Anindya, Lokawanti Al Fahna; Pestariati, Pestariati; Wisnu, Istanto (Analis Kesehatan Sains, 2021)
The threat of infectious diseases from strains of pathogenic bacteria Staphylococcus aureus and Eschericia coli is capable of causing resistance to antibiotics. The prevalence of MRSA cases was 8.2%. One of the efforts to control infections caused by antibiotic-resistant bacteria is to utilize several antimicrobial compounds derived from natural ingredients, namely propolis. Contains polyphenolic compounds and flavonoids that function as antimicrobials. The purpose of this study was to analyze the inhibition zone formed due to the antimicrobial activity of propolis extract against the growth of Staphylococcus aureus and Eschericia coli bacteria. This research was conducted in vitro at the Microbiology Laboratory of the Medical Laboratory Technology Department of Health Poltekkes Surabaya in February – April 2021. This study used the Kirby Bauer diffusion method with paper blank discs on MHA media by measuring the diameter of the inhibition zone formed from the growth of Staphylococcus aureus and Eschericia coli with units of mm. Research The concentration of propolis extract used was 5%, 10%, 15%, and 20%. In this study, it was concluded that propolis extract can be used as an antimicrobial compound, there is a different effect of concentration of propolis extract on Staphylococcus aureus from Eschericia coli. Data analysis on the Kruskal Wallis test has a value of 0.004 (<0.05) which indicates that there is a significant difference between each concentration of propolis extract both against Staphylococcus aureus and Eschericia coli. The effect of the effective concentration is at a concentration of 20% against Staphylococcus aureus which has an average inhibition zone diameter of 13 mm while that of Eschericia coli is 22.5 mm.